2019
DOI: 10.1530/rep-18-0495
|View full text |Cite
|
Sign up to set email alerts
|

Multiple superovulations alter histone modifications in mouse early embryos

Abstract: It is demonstrated that repeated superovulation has deleterious effects on mouse ovaries and cumulus cells. However, little is known about the effects of repeated superovulation on early embryos. Epigenetic reprogramming is an important event in early embryonic development and could be easily disrupted by the environment. Thus, we speculated that multiple superovulations may have adverse effects on histone modifications in the early embryos. Female CD1 mice were randomly divided into four groups: (a) spontaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 65 publications
1
10
0
Order By: Relevance
“…For instance, a study showed that combined PMSG and HCG did not alter the fertility ability of ovulated egg and the proportion of offspring obtained from 2-cell embryo transfer in rats [ 48 ]. While other study concluded that the ability of fertilized oocyte developing to embryo decreased after multiple gonadotropic stimulation [ 49 ]. Embryo development is mainly characterized by epigenetic re-programming.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a study showed that combined PMSG and HCG did not alter the fertility ability of ovulated egg and the proportion of offspring obtained from 2-cell embryo transfer in rats [ 48 ]. While other study concluded that the ability of fertilized oocyte developing to embryo decreased after multiple gonadotropic stimulation [ 49 ]. Embryo development is mainly characterized by epigenetic re-programming.…”
Section: Discussionmentioning
confidence: 99%
“…Embryo development is mainly characterized by epigenetic re-programming. Gonadotropic stimulation can downregulate the acetylation level of histone 4 at lysine 12 (H4K12ac) in the early embryos [ 49 ]. Although superovulation causes average global DNA methylation changes of embryos in mice, additional experiment is needed to verify the result since they did not have repetitive samples [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…We compared the outcomes of using superovulated zygotes either from natural mating or IVF for producing GM mice by CRISPR-Cas9 technology. C57BL/6J mice were administrated with eCG-hCG or IAS-hCG and the mouse embryo development, which may result in the introduction of DNA methylation errors (Marshall and Rivera 2018;Tang et al 2019;Yu et al 2019). It is also reported that higher genome and Grb10 (an imprinted gene) methylation, and variable mRNA expression were observed during superovulation, together with reduced blastocyst cell numbers (Chen et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Although the agouti mouse is sensitive to environmental factors, the fact that we did not find differences in coat color after superovulation does not rule out the possibility that additional DNA methylation changes exist or that other imprinted loci might show abnormal methylation. For example, it has been shown that multiple rounds of superovulation may result in histone modifications of developing embryos (40). In addition, superovulation has been shown to alter imprinting marks in oocytes and embryos in a dose-dependent manner (10) because of abnormal methylation maintenance during preimplantation development (9).…”
Section: Figurementioning
confidence: 99%